Spontaneous haemothorax in juvenile dogs: a case series. (2nd January 2019) - Stallwood, Jennifer; Allen, Shelley; Allerton, Fergus; Adamantos, Sophie; Black, Vicki
Abstract : Objectives: To describe the clinical features, treatment, and outcome of juvenile dogs presenting with spontaneous haemothorax. Methods: Retrospective multi-centre referral-based study. Hospital databases were searched for dogs aged 1–24 months with a diagnosis of spontaneous haemothorax. Dogs were defined as having spontaneous haemothorax provided there was no history of trauma, evidence of a coagulopathy or intrathoracic neoplastic mass. Data extracted for analysis included signalment, history, investigation findings, treatment, and outcome. Results: Seven dogs from two referral centres were identified. Median age was 11 months (range 3.5–20 months); four of the seven were female. There were two Chihuahuas and two Whippets; remaining breeds were represented once. Commonly reported clinical signs included lethargy ( n =7) and pyrexia ( n =6). Thymic pathology was suspected in six dogs based on thoracic imaging. Three dogs required surgical management and four were managed conservatively. Histopathology of thymic tissue was available from the surgically managed dogs and compatible with thymic haemorrhage in all cases. Two out of three dogs managed surgically died; recorded reasons were phrenic nerve dysfunction secondary to thoracotomy and acute lung injury following mechanical ventilation. All four dogs managed conservatively survived with no recorded recurrence. Impact: Spontaneous haemothorax can occur in young dogs. Pyrexia was a common feature although causality is not established. The outcome with conservative management appeared to be superior to surgery in this small cohort of dogs.